PEMBUATAN PAKAN IKAN BERBAHAN BAKU LOKAL DARI TEPUNG IKAN RED DEVIL DANAU SENTANI DI KABUPATEN JAYAPURA PROVINSI PAPUA - John Dominggus Kalor (LPPM Uncen, 2017)
The manufacture of fish feed activities of local raw materials of fishmeal red devil (Amphilphus labiatus) was performed in Beringin fish farming group at, Jl. Ayapo Sentani, on 13 to 15 June 2016. Using 2 forms and methods of activities, namely classroom activities with a lecture and outside the classroom with practical methods. The main raw material in the manufacture of feed is fishmeal red devil of Lake Sentani. The red devil fish for fishmeal has been found to have high nutrition, as well as become a pest to farmers and be a competitor fish economical and endemic species in the lake Sentani, as well as maintaining the status of bio-ecology of Lake Sentani. These fish feed production, using 4 stages (1) flouring red devil fish meat, (2) early pecampuran, (3) manufacture of pellets, (4) Packaging. Hasli obtained by the fish farmers may eventually be able to make fish feed made from local flour quality red devil fish as feed supplement for fish farmed in cages in Lake Sentani. Keywords: feed, fish meal, Red Devil, and Lake Sentani